Workaholism in management positions of a public education institution - Garcia, Kelly Alves (2023)
The paper aimed to analyze workaholism factors in the work of civil servants who occupy management positions at the Natal-Central Campus of the Federal Institute of Education, Science and Technology of Rio Grande do Norte. This is a descriptive research that involved a universe of 40 servers that responded to the DUWAS-16+PTD scale. The results showed servers didn’t notice when they worked overtime. Specific cases of workaholic servants were identified, which can contribute to a more direct action by the organization, by establishing strategies to deal with this problem.